Ethanol Extracts Test of Kumis Kucing (Orthosiphon sp.) Leaves as Natural Preservative of Wood - Abdul Azis; T.A. Prayitno; Sutjipto A Hadikusumo; Mahdi Santoso (Jurnal Ilmu Kehutanan)
The utilization of plants as a natural preservative agent of wood has not much been explored although the amount and kind of plants are relatively abundant. This study aims to determine the effectiveness of the extract of kumis kucing (Orthosiphon sp.) plant at the extract concentration to solvent of 1:12 , 1:8 and 1:4 against the dry wood termites (Cryptotermes sp.). The tested parameters were termite mortality, mass loss, and degree of damage of the test samples (filter paper). Research was carried out by impregnating the ethanol extract of the leaves and twigs mixtures in the filter papers and then the papers were fed to dry-wood termites. Data were analyzed by analysis of variance. The analysis of variance showed that treatment concentration has a highly significant effect to the mortality levels of the termites. Further, at the concentration of 1:4, the extract exhibited the highest efficacy (mortality of 65 % and mass loss of 2.71 %) and the lowest levels were shown by the controls or 0 (zero) concentration (mortality of 1 % and mass loss of 37.86 %). The concentration of the extract also affected the degree of damage. The higher the concentration, the lower the degree of damage that occurred. The degree of damage due to termite attacks at the treatment from the lowest (1:12) to the highest (1:4) concentration could be classified as heavy to light. Thus, ethanol extract of the kumis kucing at concentration of 1:4 is potent for wood preservatives because it could reduce the degradation of cellulosic materials due to dry wood termites.